Process evaluation of co-designed interventions to improve communication of positive newborn bloodspot screening results - Stephen Morris; Ellinor Olander; Jane Chudleigh; Mandy Bryon; Pru Holder; Kevin Southern; Louise Moody; Fiona Ulph; Alan Simpson; Francesco Fusco; James R Bonham (BMJ Open)
Objective To implement and evaluate co-designed interventions to improve communication of positive newborn bloodspot screening results and make recommendations for future research and practice.Design A process evaluation underpinned by Normalisation Process Theory.Setting Three National Health Service provider organisations in England.Participants Twenty-four healthcare professionals (7 newborn screening laboratory staff and 24 clinicians) and 18 parents were interviewed.Interventions Three co-designed interventions were implemented in practice: standardised laboratory proformas, communication checklists and an email/letter template.Primary outcome measures Acceptability and feasibility of the co-designed interventions.Results Auditing the implementation of these interventions revealed between 58%–76% of the items on the laboratory proforma and 43%–80% of items on the communication checklists were completed. Interviews with healthcare professionals who had used the interventions in practice provided positive feedback in relation to the purpose of the interventions and the ease of completion both of which were viewed as enhancing communication of positive newborn bloodspot screening results. Interviews with parents highlighted the perceived benefit of the co-designed interventions in terms of consistency, pacing and tailoring of information as well as providing reliable information to families following communication of the positive newborn bloodspot screening result. The process evaluation illuminated organisational and contextual barriers during implementation of the co-designed interventions in practice.Conclusion Variations in communication practices for positive newborn bloodspot screening results continue to exist. The co-designed interventions could help to standardise communication of positive newborn screening results from laboratories to clinicians and from clinicians to parents which in turn could improve parents’ experience of receiving a positive newborn bloodspot screening result. Implementation highlighted some organisational and contextual barriers to effective adoption of the co-designed interventions in practice.Trial registration number ISRCTN15330120.